Influence of rice growth on the fate of polycyclic aromatic hydrocarbons in a subtropical paddy field: A life cycle study. (January 2015) - Wang, Yan; Wang, Shaorui; Luo, Chunling; Xu, Yue; Pan, Suhong; Li, Jun; Ming, Lili; Zhang, Gan; Li, Xiangdong
Highlights: Sewage irrigation and straw burning were two main sources for PAHs in paddy fields. The concentrations of PAHs in rice leaves decreased during the heading stage. Rice growth can reduce PAHs in surface soil at a rate of ∼5 ng PAHs g −1  soil d −1 . Abstract: We measured the concentrations and profiles of polycyclic aromatic hydrocarbons (PAHs) in the soil, water, and rice tissues from a typical subtropical paddy system at various stages of rice growth over two growing seasons. Rice growth had a significant impact on the distribution and dissipation of PAHs in the paddy field. While rice was growing, the concentrations of PAHs in the soils decreased at an average decline rate of 5.3 ± 2.9 ng PAHs g −1  soil d −1, whereas, the concentrations of PAHs in rice tissues increased with growth time. However, the concentrations of PAHs in the rice leaves decreased during the heading stage of both two growing seasons. PAH profiles in soil, water, and different rice tissues also showed different patterns with the growing time of rice. Irrigation water was a significant source of PAHs to the paddy field. Rice growth enhanced the dissipation and transport of PAHs in the paddy system, while the sewage irrigation and straw burning after harvest added or returned PAHs to the system. For food safety precaution, sewage irrigation and straw burning should be well monitored and controlled.